الوهم عند الفلاسفة (نماذج مختارة) - فاطمة صلاح عبد الحسن, د. (لارك, 2024)
المستخلص :      الوهم : لغةً، هو الظنُّ الفاسد والخداع الحسِّيُّ وكلُّ ما هو غير مطابق للواقع..   ويعرف في كتاب التعريفات هو إدراك المعنى الجزئي المتعلق بالمعنى المحسوس ، وبأنه قوة جسمانية للإنسان محلها آخر التجويف الأوسط من الدماغ، من شأنها إدراك المعاني الجزئية المتعلقة بالمحسوسات، كشجاعة زيد وسخاوته، وهذه القوة هي التي تحكم بها الشاة أن الذئب مهروب عنه، وأن الولد معطوف عليه ، وهذه القوة حاكمة على القوى الجسمانية كلها، مستخدمة إياها استخدام العقل للقوى العقلية بأسرها ، اما الوهمي المتخيل هو الصورة التي تخترعها المتخيلة بأستعمال الوهم اياها كصورة الناب او المخلب في المنية المشبهة بالسبع ، اما الوهميات فهي قضايا كاذبة يحكم بها الوهم في أمور غير محسوسة كالحكم بأن ما وراء العالم فضاء لا يتناهى والقياس المركب منها يسمى سفسطة ( الجرجاني ، الشريف علي بن محمد، 1306، باب الواو )أن اصح التعبير نجد أن اول من ابتكر مفهوم الوهم من الفلاسفة المسلمين الفارابي الذي عرفهُ بقولهِ " أن من القوى الباطنة قوة تسمى وهماً وهي التي تدرك من المحسوس ما لا يحس ،مثل القوة التي في الشاة إذا تشبحت صورة الذئب في حاسة الشاة تشبحت عداوتهُ ورداءتهُ فيها ،إذ كانت الحاسة لا تدرك ذلك " كذلك أبن سينا عرفهُ بقولهِ " قوة تدرك المعاني الجزئية الموجودة في المحسوسات " (نجاتي،1980،ص181) .أما بيكون يستخدم كلمة "idola" بمعناها الحرفي الذي كان يستخدمه اليونانيون للكلمة اليونانية المقابلة لها (eidolon)، والذي يشير إلى ضرب من الوهم " illusion " أو المظهر الزائف ،وليس بمعنى الصنم أو الوثن المعبود.( بيكون ، 2013،ص28)فمن هذا المنطلق درسنا الوهم عند الفلاسفة نماذج مختارة بصورة خاصة بدءً من الفلسفة اليونانية المتمثلة بالفيلسوف افلاطون وارسطو مروراً بالفلسفة الاسلامية المتمثلة بالفارابي وأبن سينا والحديثة المتمثلة بفلاسفتها فرنسيس بيكن، وسنعمل على اتباع المنهج الأستقرائي والمقارن في دراسة البحث هذا ...الكلمات المفتاحية هي ( الوهم ، الحس الباطن ، المتخيلة ، الحواس الظاهرة ) Abstract:Illusion: Linguistically, it is corrupt suspicion, sensory deception, and everything that does not correspond to reality.It is known in the book of definitions that it is the perception of the partial meaning related to the tangible meaning, and that it is a physical power of the human being located at the end of the middle cavity of the brain, which is capable of understanding the partial meanings related to the tangible things, such as Zaid’s courage and generosity, and this power is the one by which the sheep decides that the wolf has escaped from him, and that the boy is plucked. Accordingly, this force rules over all the physical faculties, using them as the mind uses all the mental faculties. As for the imagined imaginary, it is the image that the imaginary invents by using the illusion of it, such as the image of a fang or claw in a death similar to a seven. As for imaginary matters, they are false propositions by which the illusion rules in matters that are not perceptible. Such as the ruling that what is beyond the world is an infinite space, and the analogy composed of it is called sophistry (Al-Jurjani, Al-Sharif Ali bin Muhammad, 1306, Chapter Al-Waw).In the most correct expression, we find that the first to invent the concept of illusion was among the Muslim philosophers Al-Farabi, who defined it by saying, “One of the inner powers is a power called illusion, which is what perceives from the senses what is not sensed, like the power that is in a sheep. If the image of a wolf appears in the sheep’s sense, its enmity and badness appear in it.” “Since the senses do not perceive it,” Ibn Sina also defined it by saying, “A power that perceives the partial meanings found in tangible objects” (Najati, 1980, p. 181).As for Bacon, he uses the word “idola” in the literal meaning that the Greeks used for the corresponding Greek word (eidolon), which refers to a kind of illusion or false appearance, and not in the sense of an idol or idol that is worshiped. (Bacon, 2013, p. 28)From this standpoint, we studied illusion among philosophers through selected models in particular, starting with Greek philosophy represented by the philosophers Plato and Aristotle, passing through Islamic philosophy represented by Al-Farabi and Ibn Sina, and modern philosophy represented by its philosophers Francis Bacon, and we will work to follow the inductive and comparative approach in studying this research...
Keywords: الكلمات المفتاحية هي ( الوهم ، الحس الباطن ، المتخيلة ، الحواس الظاهرة )